Pengaruh Ketidakpastian Lingkungan dan Komitmen Organisasi Terhadap Kinerja Manajerial Dengan Kualitas Sistem Informasi Akuntansi Manajemen Sebagai Variabel Intervening - Gulo, Niperjaya; Astuty, Widia; Hani, Syafrida (CV. ITTC INDONESIA, 2024)
This study aims to directly test and analyze the Influence of Environmental Uncertainty, Organizational Commitment and Quality of Management Accounting Information Systems on Managerial Performance and indirectly to test and analyze directly the influence of Environmental Uncertainty and Organizational Commitment on Managerial Performance with the Quality of Management Accounting Information Systems as an Intervening Variable in Star Hotels in Medan City. The research approach uses quantitative associative. The population of this study is all 3 to 5 star hotels in Medan City, totaling 48 hotels with a total sample of 240 respondents. This study uses the Structural Equation Modeling (SEM) analysis method using SmartPLS.3 software. Based on the results of direct hypothesis testing, there is an influence of environmental uncertainty, organizational commitment and management accounting information systems on managerial performance. Indirectly, there is an influence of environmental uncertainty and organizational commitment on managerial performance mediated by management accounting information systems